Evaluation of the academic performance in Biostatistics and the disciplinary competence of mathematical thinking in university students - Pedro César Cantú Martínez; Martha Alicia Santoyo Stephano (Pontificia Universidad Católica del Perú, 2019)
It is recognized in the university education as very important statistic to apply the severety of scientific character. The objective of the research was to compare school performance in biostatistics and competition discipline of mathematical thinking in university students in the area of life sciences. The research is transverse and exploratory. It was 187 students of both genders aged between 19 to 20 years that coursed in a way regular matter. We found a significant association between those who passed the examination of Biostatistics and the level of mathematical thinking that students showed in their admission tests (value of p < 0.01). Determining if you have a high level of mathematical thinking is boasts a 90% chance of passing the test of Biostatistics.